Georgia : Technical Assistance Report-Public Sector Balance Sheet and State Owned Enterprises. (IMF Staff Country Reports; Country Report, 2020)
Georgia's public sector balance sheet (PSBS) is in relatively healthy shape, with assets exceeding liabilities, and is comparatively lean. Looking across all entities that the government controls, including the central government, local governments, the State-Owned Enterprise (SOE) sector and the National Bank of Georgia (NBG), total assets are worth 149 percent of GDP, made up of cash, loans, infrastructure, land and productive SOE assets. Liabilities are worth 81 percent of GDP, primarily comprising loans and debt of the government and SOEs. This leaves positive net worth of 68 percent of GDP, putting it in the top third of countries in the IMF's database.